Jurnal Penyuluhan: Persepsi Pembudidaya Ikan Terhadap Kompetensi Penyuluh Perikanan di Kawasan Minapolitan (Kasus di Kabupaten Cirebon, Provinsi Jawa Barat) - Ikhsan Haryadi, Siti Amanah, Suwardi Suriatna (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2014)
esearch objectives were: 1) to describe the profile fish farmers, 2 ) to analyze the perception of fish farmers towards competence of fisheries extension worker, and 3 ) to analyze the relationship between the profile of fish farmers and fisheries extension services towards of fish farmers perceptions of competence of fisheries extension workers. The study was conducted in Cirebon regency, West Java Province.